Advances in the development of therapeutic strategies against COVID-19 and perspectives in the drug design for emerging SARS-CoV-2 variants - Jialing Yin; Chengcheng Li; Chunhong Ye; Zhihui Ruan; Yicong Liang; Yongkui Li; Jianguo Wu; Zhen Luo (Computational and Structural Biotechnology Journal, 2022)
Since Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was identified in late 2019, the coronavirus disease 2019 (COVID-19) pandemic has challenged public health around the world. Currently, there is an urgent need to explore antiviral therapeutic targets and effective clinical drugs. In this study, we systematically summarized two main therapeutic strategies against COVID-19, namely drugs targeting the SARS-CoV-2 life cycle and SARS-CoV-2-induced inflammation in host cells. The development of above two strategies is implemented by repurposing drugs and exploring potential targets. A comprehensive summary of promising drugs, especially cytokine inhibitors, and traditional Chinese medicine (TCM), provides recommendations for clinicians as evidence-based medicine in the actual clinical COVID-19 treatment. Considering the emerging SARS-CoV-2 variants greatly impact the effectiveness of drugs and vaccines, we reviewed the appearance and details of SARS-CoV-2 variants for further perspectives in drug design, which brings updating clues to develop therapeutical agents against the variants. Based on this, the development of broadly antiviral drugs, combined with immunomodulatory, or holistic therapy in the host, is prior to being considered for therapeutic interventions on mutant strains of SARS-CoV-2. Therefore, it is highly acclaimed the requirements of the concerted efforts from multi-disciplinary basic studies and clinical trials, which improves the accurate treatment of COVID-19 and optimizes the contingency measures to emerging SARS-CoV-2 variants.